Work-based learning design for students with disabilities in vocational high schools - Suyitno, Suyitno; Purwoko, Riawan Yudi; Widiyono, Yuli; Jatmoko, Dwi; Setuju, Setuju; Marsono, Marsono (Edelweiss Applied Science and Technology, 2025)
Education for students with disabilities is urgently needed as part of fulfilling educational equality. This research is motivated by the lack of learning models that focus on students with disabilities, particularly Work-Based Learning for vocational high school students. The purpose of this research is to analyze the needs and develop a design for Work-Based Learning instructional tools for Vocational High School students with special needs. This research method uses the Borg and Gall model combined with the Dick and Carey instructional model, making the stages more contextual and providing a comprehensive overview. The subjects of this research are Vocational High School students from two provinces, namely Central Java and the Special Region of Yogyakarta, specifically students with special needs, including those with disabilities. The trial stages in this research start with evaluations by subject matter experts, media experts, and instructional design experts. The next step involves product testing, which includes individual trials, small-group trials, and large-group trials. The results are then analyzed descriptively and qualitatively to assess the developed model. Thus, based on these results, the model developed is in accordance with needs and has the potential to be implemented at the vocational school level as a means of facilitating WBL-based learning for students with special needs in Indonesia.